Stability of cassava plants at the DNA level after retrieval from 10 years of in vitro storage - Angel, F.; Barney, Victoria E.; Tohme, Joseph M.; Roca, W. (Springer, 1996)
Cassava (Manihot esculenta Crantz) germplasm collections are conventionally maintained by continuous vegetative propagation in the field. Tissue culture techniques provide a more convenient way to conserve germplasm. The cassava in vitro gene bank held in trust at CIAT comprises nearly 6000 accessions. A study was carried out to determine whether any DNA rearrangements resulting from in vitro storage under slow growth could be detected by molecular analysis in retrieved plants. RFLPs with homologous probes, RAPDs with twenty primers and DNA fingerprinting with M13 probe were tested to detect variation at DNA level in cassava plants after ten-years in vitro storage. The molecular marker data obtained in this study supports the stability of the cassava germplasm under the in vitro storage conditions described in this work.